Genetic analysis of radiation resistance in Haloferax volcanii - Hayes-Smith, Callum N. (2024)
Archaea,considered as the third domain of life alongside bacteria and eukaryotes, represent a highly diverse group of organisms. Attention to archaeal DNA repair pathways has been considerable for a long time and many archaeal species inhabit extreme environmental niches where there is a higher rate of genomic insult. It is therefore thought that such archaea possess efficient and robust novel DNA repair pathways, allowing survival in such conditions. Such extreme conditions can also be found beyond Earth, such as on the surface of Mars and investigation into DNA repair in the archaea represents a pivotal stepping stone to understanding how organisms adapt to “Martian” conditions. In the work presented here, the gene encoding a XerCD-like integrase, found within the integrated prophage on the main chromosome of Haloferax volcanii was isolated from a genomic library and overexpression leads to increased resistance to genotoxic stress imposed by ultraviolet light and mitomycin C. Deletion of this gene does not impact the growth rate or sensitivity to DNA damaging agents, likely due to the presence of an additional eleven homologs within the genome. Deletion of the entire prophage region does not delete all XerCD homologs, yet shows an even larger increase in cell survival after UV and MMC treatment. Genetic analysis suggests that XerCD may interact, directly or indirectly, with UvrC as overexpression of XerCD somewhat mitigates the UV sensitivity seen in a UvrC deleted strain. The defect is not fully complemented, so further study is required. Previous data has shown that various XerCD-like integrases are upregulated in the presence of MMC. Real-time PCR carried out here indicates that phage induction may occur when cells are treated with DNA damaging agents, which may contribute to the cell death seen, and therefore strains deleted for the integrated prophage may be more beneficial to use for DNA damaging assays due to increased cellular survival. Replication Protein A transcripts are upregulated in response to MMC, aiding in interstrand crosslink repair. The interplay between XerCD-like integrases, that usually function in DNA replication, and DNA repair warrants further study.